PENGARUH GENDER, USIA, DAN PENDIDIKAN DIREKTUR UTAMA TERHADAP KINERJA PERUSAHAAN SEKTOR INDUSTRI DI BURSA EFEK INDONESIA - Jusuf, A An Arief; Sebastian, Novianto; Sutrisno, Marshela (Jurnal Bisnis Terapan, 2024)
The manufacturing industry plays a central role in the economies of developing countries, including Indonesia. Financial performance significantly impacts the assessment of a company's value. This research aims to analyze and gain a deeper understanding of how the gender, age, and educational level of Chief Executive Officers (CEOs) influence the performance of companies listed in the industrial sector on the Indonesia Stock Exchange (IDX). The characteristics of the study's population include companies in the industrial sector listed on the main board and development board of the IDX, which have published annual reports during the period 2012-2022. The data analysis methods employed involve pooled ordinary least squares and quantile regression. The Hannan-Quinn criteria are utilized to select the best equations for interpretation of the hypothesis testing results. Equations using quantile regression are selected for hypothesis testing. From the hypothesis testing results in this study, it can be concluded that the gender of the CEO has an impact on company performance, while the age and educational level of the CEO do not affect company performance. A negative trend is identified, where male CEOs tend to have a lower impact on company performance compared to their female counterparts in the CEO position.